1986
DOI: 10.1093/infdis/154.5.858
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinated Children Get Milder Measles Infection: A Community Study from Guinea-Bissau

Abstract: We studied the occurrence of measles in vaccinated children from an urban area of Guinea-Bissau where measles causes high mortality. Vaccinated children who developed measles required more-intense exposure to become infected (they had a higher ratio of secondary cases [infected in the house] to index cases [infected outside the house]), had a lower mortality among secondary cases, and were less infectious (they generated fewer secondary cases than did unvaccinated children with measles). The attack rate among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
3

Year Published

1988
1988
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 17 publications
5
43
0
3
Order By: Relevance
“…Therefore, interpretation of our data should take into account these limitations which are consequences of the passive surveillance system. However, we believe that the information obtained by the MOIF were reasonably reliable because our results agreed well with previous findings in terms of age distribution, the negative association of vaccination history with symptoms, and seasonal trend [14][15][16].…”
Section: Epidemiologysupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, interpretation of our data should take into account these limitations which are consequences of the passive surveillance system. However, we believe that the information obtained by the MOIF were reasonably reliable because our results agreed well with previous findings in terms of age distribution, the negative association of vaccination history with symptoms, and seasonal trend [14][15][16].…”
Section: Epidemiologysupporting
confidence: 90%
“…Our figure of 68n6 % for the 12-23 months age group would suggest the necessity for further investigations such as a cohort or case-control study to confirm the low measles VE in Malawi. Table 2 shows that vaccinated measles cases were less likely to develop cough, diarrhoea or pneumonia, which is consistent with the evidence that vaccinated children experience milder measles infections [15].…”
Section: Misdiagnosissupporting
confidence: 82%
“…Aaby et al [1986] demonstrated that previously vaccinated persons who develop classic measles infection are less contagious than unvaccinated persons with classic measles. It is possible that measles-infected persons with mild or no symptoms are even less likely to transmit measles; these persons may have better immunity prior to infection and a shorter duration of infection than previously vaccinated persons who develop classic measles.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized that clinical criteria cannot be used alone to rule out measles infection 6 . However, if measles virus transmission had been occurring, unvaccinated individuals and a small proportion of vaccinated individuals would have been expected to develop classical measles symptoms 21,23 . While individuals with asymptomatic or vaccine-modified measles may be less likely to infect others 24,25 , their role in sustaining low levels of measles virus transmission is unclear 21,26,27 .…”
Section: Discussionmentioning
confidence: 99%